A porous negative oxygen ion releasing material, a preparation method and application thereof

CN118420371BActive Publication Date: 2026-10-09FAIRYS BOX (SHENZHEN) BIOTECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410522958.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-28
Publication Date
2026-10-09
Estimated Expiration
2044-04-28

AI Technical Summary

Technical Problem

[0004]为了克服上述现有技术的缺点,本发明的目的之一在于提供一种多孔负氧离子释放材料及其制备方法和应用,以解决现有技术制备工艺复杂,烧结能耗高,生产周期长,以及制备的材料孔结构显孔率以及抗压强度都较低的技术问题

Benefits of technology

[0024] This invention uses tourmaline powder and cerium oxide powder as the main raw materials, adding a pore-forming agent, to prepare porous negative oxygen ion releasing materials through a low-cost, low-energy-consumption cold sintering technology. The cold sintering method used in this invention is simple to operate and can achieve rapid sintering of ceramics at temperatures below 300℃ (150–300℃). Its sintering energy consumption is only about 1/100 of that of traditional sintering technologies, offering significant advantages in energy conservation and environmental protection. Furthermore, the low temperature and short time (20–120 min) of cold sintering effectively inhibit excessive growth of ceramic grains, facilitating an increase in the specific surface area of ​​the material and increasing the amount of negative ions released.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118420371B_ABST
    Figure CN118420371B_ABST
Patent Text Reader

Abstract

The application discloses a kind of porous negative oxygen ion release material and its preparation method and application, select tourmaline powder and cerium oxide powder as main raw material, add pore-forming agent, prepare porous tourmaline material, i.e.porous negative oxygen ion release material by cold sintering method.The cold sintering temperature of the application is low, time is short, can effectively inhibit the excessive growth of ceramic grain, which makes the porosity and specific surface area of material be improved, so as to increase the negative ion release amount.The method overcomes the problems of high energy consumption and long preparation period of traditional technology, greatly reduces the cost of porous negative oxygen ion release material.The porous negative oxygen ion release material prepared by the application can be applied to small electric appliances such as electric fan, humidifier, atomizer, etc.When the electric appliance works, the air flow rate around the porous negative oxygen ion release material increases, and the negative oxygen ion release amount is further improved.This kind of device has broad application prospect in the fields of daily necessities, medical treatment, environmental protection, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of inorganic non-metallic material preparation, specifically relating to a porous negative oxygen ion releasing material, its preparation method, and its application. Background Technology

[0002] Negative oxygen ions, also known as "air vitamins," are an important indicator of air quality. They can activate cells, regulate the body's ion balance, inhibit bacterial infections, and purify the air, greatly benefiting human health and the quality of the living environment. Negative oxygen ion generators are devices that use high-voltage direct current to produce corona discharge. While they can release negative oxygen ions at high speeds, they also produce ozone, which is harmful to human health. In recent years, researchers have discovered that tourmaline possesses unique properties such as piezoelectricity, pyroelectricity, conductivity, far-infrared radiation, and the ability to release negative oxygen ions. As a healthy material for releasing negative oxygen ions, it has broad application prospects in daily necessities, medical care, and environmental protection.

[0003] The performance of tourmaline products in releasing negative oxygen ions is closely related to their specific surface area and porosity. Therefore, the control and design of their pore structure has become a research hotspot in recent years. Currently, many porous tourmaline products with controllable pore structures have been prepared through methods such as partial sintering, sol-gel, and the addition of pore-forming agents. However, these methods generally suffer from high sintering energy consumption and long preparation cycles, resulting in high costs for negative oxygen ion releasing materials. For example, the invention patent CN115650764A, "A Low-Temperature Sintered Porous Ceramic with Negative Ions and Its Preparation Method," uses tourmaline powder and cerium oxide powder as raw materials. It requires steps such as raw material mixing, heat treatment (900℃ for 1 hour), slurry preparation, aging, drying, and sintering (850-950℃ for 2-6 hours) to obtain the negative oxygen ion releasing material. This method is very complex, consumes a large amount of energy, and results in poor controllability of the material's pore structure, with low porosity and compressive strength. In addition, the performance of tourmaline products in releasing negative oxygen ions is affected by factors such as ambient air velocity and humidity. Therefore, designing a device to improve air flow is the key to increasing the amount of negative oxygen ions released. Summary of the Invention

[0004] To overcome the shortcomings of the prior art, one objective of this invention is to provide a porous negative oxygen ion releasing material, its preparation method, and its application, thereby solving the technical problems of complex preparation processes, high sintering energy consumption, long production cycles, and low porosity and compressive strength of the prepared materials. A second objective of this invention is to provide a negative oxygen ion releasing device that can increase the amount of negative oxygen ions released.

[0005] To achieve one of the above objectives, the present invention employs the following technical solution:

[0006] This invention discloses a method for preparing a porous negative oxygen ion releasing material, comprising: using tourmaline powder and cerium oxide powder as the main reactants, adding a pore-forming agent, mixing thoroughly and evenly, adding a solvent and grinding to form a granular mixed powder, pressing the granular mixed powder and then cold sintering it at 150-300℃ for 20-120 min to obtain the porous negative oxygen ion releasing material.

[0007] Furthermore, the preparation method of the present invention includes the following steps:

[0008] 1) Select tourmaline powder and cerium oxide powder as the main raw materials, add pore-forming agent, and mix them evenly using an agate mortar;

[0009] 2) Prepare the solvent by adding it dropwise into the mortar and grinding the mixed powder into small spherical particles;

[0010] 3) Transfer the granular mixed powder into a stainless steel mold, and apply axial pressure to the mold continuously using a semi-automatic molding machine;

[0011] 4) Set the program to heat the mold, causing the blank inside to undergo cold sintering;

[0012] 5) After sintering, the block removed from the mold is the porous negative oxygen ion releasing material.

[0013] Preferably, the pore-forming agent is ammonium bicarbonate, which is an inorganic pore-forming agent. This type of pore-forming agent decomposes or volatilizes during the ceramic sintering process, thereby forming pores in the ceramic body.

[0014] Preferably, the mass fraction ratio of tourmaline powder, cerium oxide powder and pore-forming agent is (64-83):(9-35):(1-8).

[0015] Preferably, the solvent used is 0.5 mol·L⁻¹ -1 Sodium hydroxide solution.

[0016] Preferably, during the pressing process, an axial pressure of 50–200 MPa is continuously applied.

[0017] More preferably, the granular mixed powder is transferred into a stainless steel mold, and a semi-automatic molding machine is used to continuously apply axial pressure to the stainless steel mold.

[0018] This invention discloses a porous negative oxygen ion releasing material prepared by the above-described method. The porous negative oxygen ion releasing material has an apparent porosity of 21% to 48% and a compressive strength of 16 to 80 MPa.

[0019] To achieve the second objective mentioned above, this invention discloses a negative oxygen ion releasing device that can increase the amount of negative oxygen ions released.

[0020] The negative oxygen ion releasing device of the present invention is made by adding a breathable shell to the above-mentioned porous negative oxygen ion releasing material.

[0021] This invention also discloses the application of porous negative oxygen ion releasing materials in the preparation of negative oxygen ion releasing devices, with a negative oxygen ion release rate of 5000–15000 ions / cm³. 3 .

[0022] Preferably, the negative oxygen ion releasing device is a small household appliance.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] This invention uses tourmaline powder and cerium oxide powder as the main raw materials, adding a pore-forming agent, to prepare porous negative oxygen ion releasing materials through a low-cost, low-energy-consumption cold sintering technology. The cold sintering method used in this invention is simple to operate and can achieve rapid sintering of ceramics at temperatures below 300℃ (150–300℃). Its sintering energy consumption is only about 1 / 100 of that of traditional sintering technologies, offering significant advantages in energy conservation and environmental protection. Furthermore, the low temperature and short time (20–120 min) of cold sintering effectively inhibit excessive growth of ceramic grains, facilitating an increase in the specific surface area of ​​the material and increasing the amount of negative ions released.

[0025] Furthermore, this invention selects to perform cold sintering below 300°C, therefore ammonium bicarbonate is chosen as the pore-forming agent. Ammonium bicarbonate can decompose at 100°C, making it very suitable as a pore-forming agent. Other common pore-forming agents, such as ammonium chloride, have a decomposition temperature as high as 338°C, which is not suitable for the low-temperature cold sintering process of this invention.

[0026] Compared to existing negative ion releasing materials, the porous negative ion releasing material prepared by this invention has lower cost and a greater negative ion release capacity, meeting the requirements of different products. The porous negative ion releasing material prepared by the method of this invention has a uniform internal pore structure, controllable pore shape, and high morphological repeatability, showing broad application prospects in daily necessities, medical, and environmental protection fields.

[0027] The porous negative ion-releasing material prepared according to this invention, when fitted with a breathable outer shell, can be used to manufacture small electrical appliances such as electric fans, humidifiers, and atomizers. When these small appliances are operating, the airflow velocity around the porous negative ion-releasing material increases, further enhancing the release of negative ions. Such devices have broad application prospects in daily necessities, medical applications, and environmental protection. Attached Figure Description

[0028] Figure 1 These are macroscopic photographs of porous negative oxygen ion releasing materials;

[0029] Figure 2 This is a SEM image of a porous negative oxygen ion releasing material;

[0030] Figure 3 This invention relates to a structure for a negative oxygen ion releasing device.

[0031] Among them: 1—fan housing; 2—power switch; 3—fan blades; 4—plastic housing wrapped with porous negative oxygen ion releasing material. Detailed Implementation

[0032] To enable those skilled in the art to better understand the present invention, the technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.

[0033] It should be noted that the terms "first," "second," etc., in the specification, claims, and accompanying drawings of this invention are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such data can be interchanged where appropriate so that the embodiments of the invention described herein can be implemented in orders other than those illustrated or described herein. Furthermore, the terms "comprising" and "having," and any variations thereof, are intended to cover a non-exclusive inclusion; for example, a process, method, system, product, or apparatus that comprises a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to such processes, methods, products, or apparatus.

[0034] The present invention will now be described in further detail with reference to the accompanying drawings:

[0035] Example 1

[0036] First, using an agate mortar, mix 19.3g of tourmaline powder, 10.4g of cerium oxide powder, and 0.3g of ammonium bicarbonate evenly. Then, add 0.5mol·L⁻¹ of [unspecified ingredient] dropwise to the mortar. -1 A sodium hydroxide solution was used to grind the mixed powder into small spherical particles. The granular powder was then transferred into a stainless steel mold, and a semi-automatic molding machine was used to continuously apply an axial pressure of 200 MPa to the mold. Finally, a program was set to heat the mold, causing the blank inside to undergo cold sintering at 300℃ for 20 minutes. After sintering, the demolded block is the porous negative oxygen ion releasing material.

[0037] See Figure 3A porous negative oxygen ion releasing material is fitted with a breathable plastic shell, and the whole thing is placed in an electric fan to assemble a negative oxygen ion releasing device.

[0038] The apparent porosity of the porous negative oxygen ion releasing material was tested using the Archimedes displacement method; the microstructure of the material was characterized using a field emission scanning electron microscope; the compressive strength of the material was tested using a universal testing machine; and the average negative oxygen ion release of the electric fan was tested using a negative ion detector. Figure 1 These are macroscopic photographs of the materials. Figure 2 This is a SEM image of the material. It can be seen that the material exhibits an isotropic porous structure. Test results show that the apparent porosity of the porous negative oxygen ion releasing material is 21%, and its compressive strength is 80 MPa. The average negative oxygen ion release rate of the electric fan is 5000 ions / cm³. 3 .

[0039] Example 2

[0040] First, using an agate mortar, mix 20.6g of tourmaline powder, 8.8g of cerium oxide powder, and 0.6g of ammonium bicarbonate evenly. Then, add 0.5mol·L⁻¹ of [unspecified substance] dropwise to the mortar. -1 A sodium hydroxide solution was used to grind the mixed powder into small spherical particles. The granular powder was then transferred into a stainless steel mold, and a semi-automatic molding machine was used to continuously apply an axial pressure of 180 MPa to the mold. Finally, a program was set to heat the mold, causing the blank inside to undergo cold sintering at 260℃ for 60 minutes. After sintering, the demolded block was the porous negative ion releasing material. A breathable plastic shell was added to the porous negative ion releasing material, and the entire assembly was placed inside an electric fan to form a negative ion releasing device.

[0041] The apparent porosity of the porous negative ion-releasing material was tested using the Archimedes displacement method; the microstructure of the material was characterized using field emission scanning electron microscopy; the compressive strength of the material was tested using a universal testing machine; and the average negative ion release of the electric fan was measured using a negative ion detector. The test results show that the apparent porosity of the porous negative ion-releasing material is 25%, and the compressive strength is 58 MPa. The average negative ion release of the electric fan is 7450 ions / cm³. 3 .

[0042] Example 3

[0043] First, using an agate mortar, mix 21.8g of tourmaline powder, 7.3g of cerium oxide powder, and 0.9g of ammonium bicarbonate evenly. Then, add 0.5mol·L⁻¹ of [unspecified ingredient] dropwise to the mortar. -1A sodium hydroxide solution was used to grind the mixed powder into small spherical particles. The granular powder was then transferred into a stainless steel mold, and a semi-automatic molding machine was used to continuously apply an axial pressure of 150 MPa to the mold. Finally, a program was set to heat the mold, causing the blank inside to undergo cold sintering at 220°C for 40 minutes. After sintering, the demolded block was the porous negative ion releasing material. A breathable plastic shell was added to the porous negative ion releasing material, and the entire assembly was placed inside an electric fan to form a negative ion releasing device.

[0044] The apparent porosity of the porous negative ion-releasing material was tested using the Archimedes displacement method; the microstructure of the material was characterized using field emission scanning electron microscopy; the compressive strength of the material was tested using a universal testing machine; and the average negative ion release of the electric fan was measured using a negative ion detector. The test results show that the apparent porosity of the porous negative ion-releasing material is 30%, and the compressive strength is 43 MPa. The average negative ion release of the electric fan is 8620 ions / cm³. 3 .

[0045] Example 4

[0046] First, using an agate mortar, mix 22.9g of tourmaline powder, 5.7g of cerium oxide powder, and 1.3g of ammonium bicarbonate thoroughly. Then, add 0.5mol·L⁻¹ of [unspecified ingredient] dropwise to the mortar. -1 A sodium hydroxide solution was used to grind the mixed powder into small spherical particles. The granular powder was then transferred into a stainless steel mold, and a semi-automatic molding machine was used to continuously apply an axial pressure of 120 MPa to the mold. Finally, a program was set to heat the mold, causing the blank inside to undergo cold sintering at 200℃ for 80 minutes. After sintering, the demolded block was the porous negative ion releasing material. A breathable plastic shell was added to the porous negative ion releasing material, and the entire assembly was placed inside an electric fan to form a negative ion releasing device.

[0047] The apparent porosity of the porous negative ion-releasing material was tested using the Archimedes displacement method; the microstructure of the material was characterized using field emission scanning electron microscopy; the compressive strength of the material was tested using a universal testing machine; and the average negative ion release of the electric fan was measured using a negative ion detector. The test results show that the apparent porosity of the porous negative ion-releasing material is 36%, and the compressive strength is 28 MPa. The average negative ion release of the electric fan is 11030 ions / cm³. 3 .

[0048] Example 5

[0049] First, using an agate mortar, mix 24g of tourmaline powder, 4.2g of cerium oxide powder, and 1.8g of ammonium bicarbonate evenly. Then, add 0.5mol·L⁻¹ of [unspecified substance] dropwise to the mortar.-1 A sodium hydroxide solution was used to grind the mixed powder into small spherical particles. The granular powder was then transferred into a stainless steel mold, and a semi-automatic molding machine was used to continuously apply an axial pressure of 100 MPa to the mold. Finally, a program was set to heat the mold, causing the blank inside to undergo cold sintering at 180℃ for 100 minutes. After sintering, the demolded block was the porous negative ion releasing material. A breathable plastic shell was added to the porous negative ion releasing material, and the entire assembly was placed inside an electric fan to form a negative ion releasing device.

[0050] The apparent porosity of the porous negative ion-releasing material was tested using the Archimedes displacement method; the microstructure of the material was characterized using field emission scanning electron microscopy; the compressive strength of the material was tested using a universal testing machine; and the average negative ion release of the electric fan was measured using a negative ion detector. The test results show that the apparent porosity of the porous negative ion-releasing material is 42%, and the compressive strength is 18 MPa. The average negative ion release of the electric fan is 12,800 ions / cm³. 3 .

[0051] Example 6

[0052] First, using an agate mortar, mix 24.9g of tourmaline powder, 2.8g of cerium oxide powder, and 2.3g of ammonium bicarbonate evenly. Then, add 0.5mol·L⁻¹ of [unspecified ingredient] dropwise to the mortar. -1 A sodium hydroxide solution was used to grind the mixed powder into small spherical particles. The granular powder was then transferred into a stainless steel mold, and a semi-automatic molding machine was used to continuously apply an axial pressure of 50 MPa to the mold. Finally, a program was set to heat the mold, causing the blank inside to undergo cold sintering at 150°C for 120 minutes. After sintering, the demolded block was the porous negative ion releasing material. A breathable plastic shell was added to the porous negative ion releasing material, and the entire assembly was placed inside an electric fan to form a negative ion releasing device.

[0053] The apparent porosity of the porous negative ion-releasing material was tested using the Archimedes displacement method; the microstructure of the material was characterized using field emission scanning electron microscopy; the compressive strength of the material was tested using a universal testing machine; and the average negative ion release of the electric fan was measured using a negative ion detector. The test results show that the apparent porosity of the porous negative ion-releasing material is 48%, and the compressive strength is 16 MPa. The average negative ion release of the electric fan is 15,000 ions / cm³. 3 .

[0054] In summary, this invention is the first to utilize cold sintering technology to prepare porous negative oxygen ion releasing materials. It enables rapid sintering of tourmaline powder at temperatures below 300℃, significantly reducing sintering energy consumption and saving costs. Cold sintering also effectively inhibits excessive growth of ceramic grains, increases the specific surface area of ​​the material, and increases the amount of negative ions released. Furthermore, the porous negative oxygen ion releasing material prepared by this invention can be applied to small electrical appliances such as electric fans, humidifiers, and atomizers. When these appliances are operating, the air velocity around the porous negative oxygen ion releasing material increases, further enhancing the release of negative oxygen ions.

[0055] The above content is only for illustrating the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. Any modifications made to the technical solution based on the technical concept proposed in this invention shall fall within the scope of protection of the claims of this invention.

Claims

1. A method for preparing a porous negative oxygen ion releasing material, characterized in that, include: Tourmaline powder and cerium oxide powder are used as the main reactants, and ammonium bicarbonate is added as a pore-forming agent. The mixture is thoroughly mixed and homogeneous, wherein the mass fraction ratio of tourmaline powder, cerium oxide powder and pore-forming agent is (64-83):(9-35):(1-8). Solvent is added and the mixture is ground to form a granular mixed powder. The granular mixed powder is then pressed and cold-sintered at 150-300℃ for 20-120 minutes to obtain a porous negative oxygen ion releasing material.

2. The preparation method of the porous negative oxygen ion releasing material according to claim 1, characterized in that, The solvent used was a 0.5 mol·L⁻¹ sodium hydroxide solution.

3. The preparation method of the porous negative oxygen ion releasing material according to claim 1, characterized in that, During the pressing process, an axial pressure of 50–200 MPa is continuously applied.

4. The preparation method of the porous negative oxygen ion releasing material according to claim 3, characterized in that, The granular mixed powder is transferred into a stainless steel mold, and a semi-automatic molding machine is used to continuously apply axial pressure to the stainless steel mold.

5. A porous negative oxygen ion releasing material prepared by the preparation method according to any one of claims 1 to 4, characterized in that, The porous negative oxygen ion releasing material has an apparent porosity of 21%–48% and a compressive strength of 16–80 MPa.

6. The application of the porous negative oxygen ion releasing material according to claim 5 in the preparation of a negative oxygen ion releasing device, characterized in that, The release rate of negative oxygen ions is 5,000 to 15,000 per cubic centimeter.

7. The application as described in claim 6, characterized in that, The negative oxygen ion releasing device is a small household appliance.

8. A negative oxygen ion releasing device, characterized in that, It is made by adding a breathable outer shell to the porous negative oxygen ion releasing material as described in claim 5.

Citation Information

Patent Citations

  • Low-temperature sintered negative ion porous ceramic and preparation method thereof

    CN115650764A

  • Tourmaline-modified powder capable of efficiently releasing negative ions and preparation method of powder

    CN109796933A

  • Preparation method of porous ceramic and atomizing core thereof

    CN112321289A

  • Method for preparing porous ceramic through low-temperature hot pressing

    CN117185787A